2019
DOI: 10.31964/mltj.v0i0.242
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Test of Black Pomegranate Peel Extract (Granati Fructus Cortex) Against Larvae of Shrimp (Artemia salina Leach)

Abstract: Toxicity test on red pomegranate has done, while in black pomegranate is not widely known. Black pomegranate peel (Granati Fructus Cortex) has some chemical ingredients such as saponins, flavonoids, tannins, and alkaloids. Alkaloids, saponins, and flavonoids are thought to be toxic at certain levels. This study aimed to determine the effects of toxic black pomegranate peel extract (Granati Fructus Cortex) against larvae of shrimp (Artemia salina Leach) indicated LC50 values below 1000 µg / ml. This study is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similarly, this extract showed the highest activity after 48 and 72 h of exposure, with LC 50 values of 156.84 and 138.12 ppm/mL, respectively. A previous study showed that Blk ethanol extract exhibited similar larvicidal activity against larvae of shrimp ( Artemia salina Leach) 47 . Following Blk, Aka extract exhibited LC 50 values of 189.02, 179.07, and 169.65 ppm/mL after 24, 48, and 72 h of exposure, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, this extract showed the highest activity after 48 and 72 h of exposure, with LC 50 values of 156.84 and 138.12 ppm/mL, respectively. A previous study showed that Blk ethanol extract exhibited similar larvicidal activity against larvae of shrimp ( Artemia salina Leach) 47 . Following Blk, Aka extract exhibited LC 50 values of 189.02, 179.07, and 169.65 ppm/mL after 24, 48, and 72 h of exposure, respectively.…”
Section: Resultsmentioning
confidence: 85%